Comparative Account of Heavy Metal Level in Two Species of Chlorophyceae Inhabiting Indian Sundarbans - Pramanick Prosenjit; Zaman Sufia; Rudra Tanmoy; Guha Arnesha; Mitra Abhijit (International Journal of Research in Chemistry and Environment (IJRCE), 2016)
We analyzed selective heavy metals (Zn, Cu and Pb) in two dominant species of family Chlorophyceae (Enteromorpha intestinalis and Ulva lactuca) in Indian Sundarbans by using AAS. The samples were collected during low tide from Gosaba, Bali Island and Jharkhali in premonsoon, monsoon and postmonsoon in 2014-15. The order of heavy metal accumulation is E. intestinalis > U. lactuca. In both the species, the order of metal accumulation of heavy metals is Zn > Cu > Pb. The seasonal sequence of accumulation is monsoon > postmonsoon > premonsoon. ANOVA carried on the observed data reflects pronounced variations between stations and seasons, but no significant variation between species is observed.